Morphological and Anatomical Study of Some Species of Ziziphus L. (Rhamnaceae) Growing in Iraq - AL-Hadeethi, Muazaz A. Hasan; Al-shami, Sinan S. Dheyab; AL-Taie, Ali T.; Hashim, Rasha Tareq (International Journal of Membrane Science and Technology, 2023)
The genus Ziziphus is one of the Family Rhamnaceae and consists of more than 170 species distributed in tropical and subtropical regions. All the species in the genus are of economical and medical importance. This study was conducted to identify the morphologically and anatomically features of the genus in Iraq. The field survey was conducted across the study area where 4 species (Ziziphus jujube, Z. mauritiana, Z. nummularia and Z. spina-christi) were collected and used in the study. The result showed that there is variation in morphological and anatomical features among the species in the stem cross-section and longitudinal section of leaves also the differences appeared in the epidermis of leaves.